Um estudo de simulação a partir de dados de marcadores microssatélites em fragmentos de Luehea divaricata Mart. & Zucc. no bioma Pampa - Serrote, Caetano Miguel Lemos (2015)
The objective was to use microsatellite DNA markers in simulations to study genetic, ecological and reproductive patterns that contributed to the genetic structure of five fragments of the forest tree species Luehea divaricata Mart. & Zucc, growing in the Pampa biome (Brazil). Various rates of selfing and migration were simulated. Selection criteria included observed and expected heterozygosity, whith values of 0,52 and 0,64, respectively (based on microsatellite markers). Reproductive mode was mixed, with a predominance of outcrosses (rate = 0,7), consistent with a self-incompatibility system in this species, which reduced but did not prevent self-fertilization. Migration at the rate of 0,02, implied existence of isolation by distance between fragments, which increased inbreeding coefficients. Based on Nei s gene diversity analysis, only 6% of genetic variability was distributed among fragments, with 94% inside them, due to the high outcrosses observed. Parameters for genetic conservation, namely, Minimum Viable Population and Minimum Viable Area, determined for conservation in the short and long terms, suggested that only the Inhatinhum fragment had the potential to maintain its genetic diversity in the short term. However, in the long term, none of the fragments proved feasible, thus requiring urgent intervention to prevent a decline, with creation of ecological corridors as a useful alternative to connect fragments through gene flow. The importance of computer programs for simulation of genetic, ecological and reproductive population parameters were clearly evident, demonstrating its potential for predicting future phenomena, thereby enabling identification of priority populations for conservation.